Percussiopalpus gen. n. from Turkey, a free-living relative of cave-dwelling Thaumastocephalus, and revised placement of Thaumastocephalini (Coleoptera: Staphylinidae: Pselaphinae) - Jałoszyński, Paweł; Hlaváč, Peter; Anlaş, Si̇nan (Zootaxa, 2023)
A new genus and species, Percussiopalpus inusitatus Hlaváč & Jałoszyński gen. n. et sp. n. of the tribe Thaumastocephalini is described and illustrated, based on specimens collected in the Asian part of Turkey (Balıkesir Province). The discovery of a free-living pselaphine species morphologically closely resembling the obligate cavernicolous Thaumastocephalus Poggi et al. prompted a detailed morphological study of both genera, which results in transferring Thaumastocephalini from Batrisitae to Euplectitae.